Circulating and intraprostatic sex steroid hormonal profiles in relation to male pattern baldness and chest hair density among men diagnosed with localized prostate cancers. Issue 16 (2nd October 2017) - Zhou, Cindy Ke; Stanczyk, Frank Z.; Hafi, Muhannad; Veneroso, Carmela C.; Lynch, Barlow; Falk, Roni T.; Niwa, Shelley; Emanuel, Eric; Gao, Yu‐Tang; Hemstreet, George P.; Zolfghari, Ladan; Carroll, Peter R.; et al.
Abstract : Background: Prospective cohort studies of circulating sex steroid hormones and prostate cancer risk have not provided a consistent association, despite evidence from animal and clinical studies. However, studies using male pattern baldness as a proxy of early‐life or cumulative androgen exposure have reported significant associations with aggressive and fatal prostate cancer risk. Given that androgens underlie the development of patterned hair loss and chest hair, we assessed whether these two dermatological characteristics were associated with circulating and intraprostatic concentrations of sex steroid hormones among men diagnosed with localized prostate cancer. Methods: We included 248 prostate cancer patients from the NCI Prostate Tissue Study, who answered surveys and provided a pre‐treatment blood sample as well as fresh frozen adjacent normal prostate tissue. Male pattern baldness and chest hair density were assessed by trained nurses before surgery. General linear models estimated geometric means and 95% confidence intervals (95%CIs) of each hormone variable by dermatological phenotype with adjustment for potential confounding variables. Subgroup analyses were performed by Gleason score (<7 vs ≥7) and race (European American vs. African American). Results: We found strong positive associations of balding status with serum testosterone, dihydrotestosterone (DHT), estradiol, and sex hormone‐binding globulin (SHBG), and a weak association with elevated intraprostatic testosterone. Conversely, neither circulating nor intraprostatic sex hormones were statistically significantly associated with chest hair density. Age‐adjusted correlation between binary balding status and three‐level chest hair density was weak ( r  = 0.05). There was little evidence to suggest that Gleason score or race modified these associations. Conclusions: This study provides evidence that balding status assessed at a mean age of 60 years may serve as a clinical marker for circulating sex hormone concentrations. The weak‐to‐null associations between balding status and intraprostatic sex hormones reaffirm differences in organ‐specific sex hormone metabolism, implying that other sex steroid hormone‐related factors (eg, androgen receptor) play important roles in organ‐specific androgenic actions, and that other overlapping pathways may be involved in associations between the two complex conditions.